Chemical recycling of textile waste - Nemeša Ineta; Pešić Marija; Bozoki Valentina (Tekstilna industrija)
Chemically recycled textile waste can be used to manufacture new textile products. It can ensure up cycling process. Two groups of chemical recycling are: recycling at the polymer level and recycling at the monomer level. The basic steps of chemical recycling process are: preparation, cleaning and recycling of the waste. Chemical recycling technologies have been developed for the processing of cotton, polyester and poly-cotton. Currently, the most part of chemical recycling companies operate at their research centers and first pilot factories, and still improve their recycling methods. Chemical recycling technologies will be commercially effective in the next 5-10 years. Innovative textile waste recycling companies in Europe are: Renewcell/Circulose, Infi nite Fiber Company, SaXcell, Södra, Worn Again Technologies, Carbios (France), Erema.